Analysis of morphological errors in university research papers by female students of the Arabic language education department at Al-Raya University - Amelia, Fitri; Bakhiet, Bakri Muhammad; Chamidah, Dewi (Abjadia : International Journal of Education, 2025)
This study investigates morphological errors in academic writings by students in the Arabic Language Teaching Department at Al-Raya University. Despite the university’s strong commitment to promoting Arabic proficiency and providing an Arabic-speaking environment, students still make significant morphological errors in their research papers. These errors, especially in the use of correct word forms, significantly impact the clarity and accuracy of their work. The research identifies and classifies common morphological mistakes such as incorrect derivations, verb usage, and the application of prefixes and suffixes. Such errors can change the meaning of words, leading to incorrect interpretations of academic content. For instance, using the word "عالم" (scholar) instead of "علامة" (sign) can result in misleading conclusions. The study analyzed 20 student research papers from 2023, revealing 85 distinct morphological errors. The findings emphasize the need for more focused instruction on Arabic morphology, suggesting improvements in teaching methods and the development of academic support programs. The study aims to enhance the quality of academic writing among students by providing insights into common errors and offering recommendations to reduce these mistakes in future research.